2023
DOI: 10.3390/d15020184
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Patterns of Wolves, and Sympatric Predators and Prey Relative to Human Disturbance in Northwestern Greece

Abstract: In an era of increasing human pressure on nature, understanding the spatiotemporal patterns of wildlife relative to human disturbance can inform conservation efforts, especially for large carnivores. We examined the temporal activity and spatial patterns of wolves and eight sympatric mammals at 71 camera trap stations in Greece. Grey wolves temporally overlapped the most with wild boars (Δ = 0.84) and medium-sized mammals (Δ > 0.75), moderately with brown bears (Δ = 0.70), and least with roe deer (Δ = 0.46)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Human presence can also influence predator–prey interaction by altering their diel activity patterns (Petridou et al, 2023 ). Analysis of activity patterns revealed that prey species showed high temporal overlap with humans, whereas there was little overlap in the activity of predators with that of humans.…”
Section: Discussionmentioning
confidence: 99%
“…Human presence can also influence predator–prey interaction by altering their diel activity patterns (Petridou et al, 2023 ). Analysis of activity patterns revealed that prey species showed high temporal overlap with humans, whereas there was little overlap in the activity of predators with that of humans.…”
Section: Discussionmentioning
confidence: 99%
“…It is a very suitable method for studying the behavior of large mammals [22][23][24] . The method turns out to be very effective for research as well as for comparison of diurnal activity of multiple species in a certain area [25][26][27] .…”
Section: Monitoring In Zoology Using Camera Trapsmentioning
confidence: 99%
“…However, shifts in the wolves' space use or other factors could have influenced this effect. In Moldavia and Greece high temporal overlap of wolves and roe deer was found, however roe deer activity peaked when wolf activity decreased (Popova et al, 2018, Petridou et al, 2023. In a study looking at activity synchronisation between wolves and moose in Norway, moose activity peaked at dusk, whereas the wolves' activity peaked at dawn (Eriksen et al, 2011).…”
Section: Activity Overlapmentioning
confidence: 99%